Comparison of two Surgical Procedures in the Management of Oroantral Fistula - Channar, Kashif Ali; Shaikh, Irfan Ahmed; Soomro, Seema Naz; Memon, Abdul Bari; Jabbar, Abdul; Najam, Shahwar (Journal of Liaquat University of Medical & Health Sciences, 2021)
Objective: To compare between double layer closure and buccal advancement flap in the management of Oro-antral fistula. Methodology: This Comparative cross sectional study was conducted on 30 patients with oral antral fistula in Maxillofacial Surgery Department, Liaquat University of Medical & Health sciences Hyderabad. The study was conducted from March 2013 to February 2019. Selection of patients was made on inclusion criteria of patient having OAF for more than 15 days, irrespective of location and side. Patients who developed Oro-antral fistula (OAF) because of any pathology or its treatment, and patient having bleeding tendency were excluded. Division of two groups to avoid any bias in this study was done by using random number table. Group-I was treated with buccal advancement flap while group-II with “double layer closure “with buccal fat pad” and 2nd layer with buccal advancement. The outcome was evaluated for any postoperative complications like wound dehiscence, necrosis, infection. Results: Males and females were 67% and 33% respectively. The mean age was 35.03±9.56 years. Maxillary molars were the common site for OAF. Maxillary first molar followed by second molar site was ranked according to frequency of this condition. Buccal advancement procedure was used in group A and in this cluster 86.6% cases were successful. In Group B, a double layered closure procedure was used and the success rate was 93.3% which is statistically not significant. Conclusion: Double-layered closure using BFP with buccal advancement flap should be kept as a valuable option in mind in the management of OAF. Key Words: Buccal Advancement Flap, Oro-Antral Fistula, Buccal Fat Pad, Double Layered Closed Technique.